Family history in primary care: understanding GPs' resistance to clinical genetics — qualitative study - Mathers, Jonathan (Royal College of General Practitioners, 2010)
BACKGROUND: National and local evaluations of clinical genetics service pilots have experienced difficulty in engaging with GPs. AIM: To understand GPs' reluctance to engage with clinical genetics service developments, via an examination of the role of family history in general practice. DESIGN OF STUDY: Qualitative study using semi-structured one-to-one interviews. SETTING: The West Midlands, UK. METHOD: Interviews with 21 GPs working in 15 practices, based on a stratified random sample from the Midlands Research Practices Consortium database. Thematic analysis proceeded alongside data generation. Framework grids were constructed for comparative analytical questioning. Interpretation was framed by two explanatory models: a knowledge deficit model, and practice and professional identity model. RESULTS: There is a clear distinction between the routine use and function of family history in GPs' clinical decision making, and contrasting conceptualisations of genetics and ‘genetic conditions’. Although genetics is clearly a part of current GP practice, with acknowledgement of genetic components to multifactorial disease, this is distinguished from ‘genetic conditions’ which are seen as rare, complex single-gene disorders. Importantly, family history takes its place within a broader notion of the ‘family doctor’ that interviewees identified as a key aspect of their role. In contrast, clinical genetics was not identified as a core component of generalist practice. CONCLUSION: The likely effectiveness of educational policy interventions aimed at GPs that focus solely on knowledge deficit models, is questionable. There is a need to acknowledge how appropriate practice is constructed by GPs, within the context of accepted generalist roles and related identities.